Fontan-associated liver disease: the importance of multidisciplinary teamwork in its management - Tsuchihashi, Tomoya; Cho, Yuki; Tokuhara, Daisuke (Frontiers in Medicine, 2024)
The Fontan operation, which directly connects the inferior vena cava to the pulmonary artery, is a palliative surgery for children with a functional or anatomic single ventricle. This procedure leads to hemodynamic changes (Fontan circulation) in patients, who tend to develop congestive hepatic fibrosis characterized by sinusoidal fibrosis and dilatation beginning approximately 10 years after the procedure. In addition, in the context of severe fibrosis and cirrhosis, hepato-gastrointestinal complications including hepatocellular carcinoma, focal nodular hyperplasia, and portal hypertension can arise. Fontan-associated liver disease (FALD) encompasses the broad spectrum of liver alterations secondary to postoperative hemodynamic changes, and the effective management of FALD requires contributions from specialists in hepatology, gastroenterology, surgery, radiology, histopathology, and pediatric and adult cardiology. In this article, we outline the pathogenesis of FALD and discuss the importance of a multidisciplinary collaborative approach to its management.